Formula Media Pertumbuhan Bakteri Asam Laktat Pediococcus pentosaceus Menggunakan Substrat Whey Tahu - SAFITRI NURLAELA; TITI CANDRA SUNARTI; ANJA MERYANDINI (Jurnal Sumberdaya Hayati, 2016)
The lactic acid bacteria (LAB) and its lactic acid are commonly used to preserve the food and to extend the food’s shelf life. MRS media is a growth medium for LAB, but it is not feasible for industrial scale application. Cheaper substrate from agriculture products is therefore required, such as tofu whey, which is potential to be used as LAB medium. Tofu whey contains important components to support the LAB growth, but it needs C source (5% of glucose) and nitrogen source (1% ammonium sulphate or urea) supplementations. This study aimed to investigate the influence of N-source to Pediococcus pentosaceus growth and its capability in producing acid compounds. The result showed that addition of urea increased pH fermentation, contrarily to that ammonium sulphate supplementation. The highest bacterial growth rate (μmaks) was observed on media with urea (0.43 jam-1), while the highest acid production was occured on media with ammonium sulphate (9.13 mg/mL). Supplementation of ammonium sulphate and urea on tofu whey highly supported the growth of bacterial population for about 6.5 × 108 CFU/mL and 5.4 × 108 CFU/ mL, respectively, but still lower compared to MRS media (2.03 × 1010 CFU/mL).